التحول الرقمي لتسويق العمليات المصرفية وأثره على جودة الخدمات المصرفية المقدمة في ظل بيئة تنافسية : دراسة تطبيقية في عينة من المصارف في العراق (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               This study aims to demonstrate the impact of digital transformation on the marketing and quality of  banking services, as banking  marketing is an  essential axis on  which banking  and financial institutions depend to present their  services in a way  that satisfies  customers` requirements  and need for banking services, and to identify the most important  problems facing the application of digital trans formation  in banking  institutions in Iraq for a group   of public and private banks in the banking sector as an independent  variable, and the relationship of this to the quality ofservice and customer satisfaction as a dependent variable.This is done by preparing human resources and focusing on training the working banking staff in a manner consistent with modern global Developments for effective marketing performance for the purpose of attracting customers and meeting their needs and desires to ensure the preservation of banking stability by providing cash, liquidity, supporting the country's economy, and gaining customer confidence in the   banking system in an environment full of risks is reflected in the reputation of banking system.The descriptive and analytical approach was relied upon, and the questionnaire represented the main tool to reach the results.The researcher chose to conduct the study a sample of government and private banks in Iraq.  The study sample, which was chosen in stratified random manner, consisted of 30 banks.In addition to some deficiencies in the infrastructure and the process of spreading the culture of digital transformation, especially among customers.The study concluded with many recommendations, the most important of which is the necessity of using highly skilled human resources trained in modern technologies, developing cadres in line with digital transformation, and the necessity of giving sufficient attention to developing the infrastructure and marketing the banking service to achieve better quality, faster, and less expensive delivery of the banking service to the customer.  And gain his satisfaction.